Microbiota and inflammatory bowel disease: the dual effect mechanism of polysaccharide therapy - Yang, Jihao; Huang, Qian; Long, Jingchun; Li, Jia (Frontiers in Immunology, 2025)
Inflammatory bowel disease (IBD) is characterized by chronic intestinal inflammation, strongly influenced by gut microbiota dysbiosis, barrier dysfunction, and immune imbalance. Increasing evidence highlights natural polysaccharides as promising therapeutic agents due to their dual roles in microbiota modulation and barrier reinforcement. Polysaccharides promote the growth of beneficial bacteria such as Lactobacillus and Bifidobacterium, enhance short-chain fatty acid (SCFA) production, and repair mucosal damage by upregulating goblet cells and tight junction proteins. These effects collectively restore microbial homeostasis and attenuate inflammation. Recent advances in polysaccharide-based nanocarriers, including chitosan, alginate, and hyaluronic acid, further enhance efficacy by enabling mucoadhesion, stimuli-responsive release, and targeted delivery within the inflamed colon. Such systems improve local drug retention, reshape the gut microenvironment, and amplify the therapeutic functions of polysaccharides. This review summarizes the pathological mechanisms of IBD, the regulatory effects of polysaccharides on gut microbiota, and the emerging role of nanotechnology in optimizing their delivery. Despite encouraging preclinical evidence, challenges remain regarding structural complexity, bioavailability, and clinical translation. Clarifying structure–activity relationships and developing multi-responsive nanocarriers represent future directions. Collectively, polysaccharides and their nanoformulations hold strong potential as safe and effective strategies for IBD therapy.